Myoglobin Protects Breast Cancer Cells Due to Its ROS and NO Scavenging Properties - Quinting, Theresa; Heymann, Anna Katharina; Bicker, Anne; Nauth, Theresa; Bernardini, Andre; Hankeln, Thomas; Fandrey, Joachim; Schreiber, Timm (Frontiers in Endocrinology, 2021)
Myoglobin (MB) is an oxygen-binding protein usually found in cardiac myocytes and skeletal muscle fibers. It may function as a temporary storage and transport protein for O2, but could also have scavenging capacity for reactive oxygen and nitrogen species. In addition, MB has recently been identified as a hallmark in luminal breast cancer and was shown to be robustly induced under hypoxia. Cellular responses to hypoxia are regulated by the transcription factor hypoxia-inducible factor (HIF). For exploring the function of MB in breast cancer, we employed the human cell line MDA-MB-468. Cells were grown in monolayer or as 3D multicellular spheroids, which mimic the in vivo avascular tumor architecture and physiology with a heterogeneous cell population of proliferating cells in the rim and non-cycling or necrotic cells in the core region. This central necrosis was increased after MB knockdown, indicating a role for MB in hypoxic tumor regions. In addition, MB knockdown caused higher levels of HIF-1α protein after treatment with NO, which also plays an important role in cancer cell survival. MB knockdown also led to higher reactive oxygen species (ROS) levels in the cells after treatment with H2O2. To further explore the role of MB in cell survival, we performed RNA-Seq after MB knockdown and NO treatment. 1029 differentially expressed genes (DEGs), including 45 potential HIF-1 target genes, were annotated in regulatory pathways that modulate cellular function and maintenance, cell death and survival, and carbohydrate metabolism. Of these target genes, TMEFF1, TREX2, GLUT-1, MKNK-1, and RAB8B were significantly altered. Consistently, a decreased expression of GLUT-1, MKNK-1, and RAB8B after MB knockdown was confirmed by qPCR. All three genes of interest are often up regulated in cancer and correlate with a poor clinical outcome. Thus, our data indicate that myoglobin might influence the survival of breast cancer cells, possibly due to its ROS and NO scavenging properties and could be a valuable target for cancer therapy.